Developing estimates of frequency and intensity of exposure to three types of metalworking fluids in a population‐based case–control study of bladder cancer. Issue 8 (August 2014) - Friesen, Melissa C.; Park, Dong‐Uk; Colt, Joanne S.; Baris, Dalsu; Schwenn, Molly; Karagas, Margaret R.; Armenti, Karla R.; Johnson, Alison; Silverman, Debra T.; Stewart, Patricia A.
Abstract Background A systematic, transparent, and data‐driven approach was developed to estimate frequency and intensity of exposure to straight, soluble, and synthetic/semi‐synthetic metalworking fluids (MWFs) within a case–control study of bladder cancer in New England. Methods We assessed frequency using individual‐level information from job‐specific questionnaires wherever possible, then derived and applied job group‐level patterns to likely exposed jobs with less information. Intensity estimates were calculated using a statistical model developed from measurements and determinants extracted from the published literature. Results For jobs with probabilities of exposure ≥0.5, median frequencies were 8–10 hr/week, depending on MWF type. Median intensities for these jobs were 2.5, 2.1, and 1.0 mg/m3 for soluble, straight, and synthetic/semi‐synthetic MWFs, respectively. Conclusions Compared to case‐by‐case assessment, these data‐driven decision rules are transparent and reproducible and may result in less biased estimates. These rules can also aid future exposure assessments of MWFs in population‐based studies. Am. J. Ind. Med. 57:915–927, 2014. © 2014 Wiley Periodicals, Inc.